Advances in Hypofractionated Irradiation-Induced Immunosuppression of Tumor Microenvironment - Wang, Yuxia (Frontiers in Immunology, 2021)
Hypofractionated radiotherapy is external beam irradiation delivered at higher doses in fewer fractions than conventional standard radiotherapy, which can stimulate innate and adaptive immunity to enhance the body’s immune response against cancer. The enhancement effect of hypofractionated irradiation to immune response has been widely investigated, which is considered an approach to expand the benefit of immunotherapy. Meanwhile, increasing evidences suggested that hypofractionated irradiation may induce or enhance the suppression of immune microenvironments. However, the suppressive effects of hypofractionated irradiation on immunomicroenvironment and the molecular mechanisms involved in these conditions are largely unknown. In this context, we summarized the immune mechanisms associated with hypofractionated irradiation, highlighted the advances in its immunosuppressive effect, and further discussed the potential mechanism behind this effect. In our opinion, besides its immunogenic activity, hypofractionated irradiation also triggers homeostatic immunosuppressive mechanisms which may counterbalance antitumor eﬀects. And this may suggest that a combination with immunotherapy could possibly improving the curative potential of hypofractionated radiotherapy.